Volleyball injuries presenting in casualty: a prospective study - Solgard, L.; Nielsen, A. B.; Moeller-Madsen, B.; Jacobsen, B. W.; Yde, J.; Jensen, J. (British Journal of Sports Medicine, 1995)
Im Jahr 1986 wurden in 2 Unfallstationen in Arhus alle Sportverletzungen prospektiv erfaßt (n=5222). Die Volleyballverletzungen lagen mit 5,3 % an 4. Stelle der Sportverletzungen und betrugen n=287. 3 Jahre nach Verletzung wurde durch Befragung eine Einschätzung der Rehabilitationsperiode und der Verletzungsfolgen vorgenommen. Die Verletzungshäufigkeit betrug 1,9 Verletzungen/1000 Einwohner/Jahr. Die häufigsten Verletzungen waren Hand-, Finger- und Fußgelenksverstauchungen. Weibliche Spieler hatten signifikant mehr Hand-/Fingerverletzungen als männliche Spieler, die mehr Fußgelenk-/Fußverletzungen aufwiesen. Knie- (6 %) und Fußgelenkverletzungen (31 %) bewirkten den längsten Trainingsausfall. Es traten relativ wenig chronische Verletzungen auf. During 1986, all sports injuries (n = 5222) were prospectively recorded at the two casualty departments in Arhus, Denmark. Volleyball injuries (n = 278) accounted for 5.3% of all sports injuries. An evaluation of the rehabilitation period and the consequences of the injuries was undertaken by questionnaire three years after the injury. The injury incidence was 1.9 injuries/1000 inhabitants/year. Hand, finger, and ankle sprains were the most frequent injuries. Female players had significantly more hand/finger injuries than male players, who incurred more ankle/foot injuries. Knee (6%) and ankle injuries (31%) were responsible for the longest duration of absence from sports participation. There were relatively few chronic injuries. The study suggests the need to enhance prophylactic measures with regard to blocking and overhand pass techniques, in order to reduce the number and extent of ankle and hand/finger injuries.